2001
DOI: 10.1603/0022-0493-94.6.1369
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of Adult European Corn Borer (Lepidoptera: Crambidae) Within and Proximal to Irrigated and Non-irrigated Corn

Abstract: The European corn borer, Ostrinia nubilalis (Hu¨ bner), causes economic damage to corn, Zea mays L., throughout the Corn Belt. Because this insect has become the primary target of Bacillus thuringiensis Berliner (Bt) transgenic corn, current efforts addressing the management of O. nubilalis resistance to Bt corn require information on adult European corn borer dispersal and factors affecting its dispersal. In 1998 we conducted markÐreleaseÐrecapture, releaseÐrecapture, and caged-mating studies to directly meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
73
0
7

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 17 publications
(34 reference statements)
1
73
0
7
Order By: Relevance
“…Surveys of Þrst-ßight O. nubilalis distributions among grassy ditches in central Iowa suggest that although some adults may colonize the grass adjacent to their presumed natal cornÞelds, they do not remain there long (Sappington 2005). Evidence is accumulating that suggests the propensity of O. nubilalis to disperse is signiÞcant and that most adults may disperse from their natal Þeld with only a few remaining nearby for Ͼ1Ð2 d (Showers et al 1976(Showers et al , 2001Hunt et al 2001, Fig. 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys of Þrst-ßight O. nubilalis distributions among grassy ditches in central Iowa suggest that although some adults may colonize the grass adjacent to their presumed natal cornÞelds, they do not remain there long (Sappington 2005). Evidence is accumulating that suggests the propensity of O. nubilalis to disperse is signiÞcant and that most adults may disperse from their natal Þeld with only a few remaining nearby for Ͼ1Ð2 d (Showers et al 1976(Showers et al , 2001Hunt et al 2001, Fig. 3.…”
Section: Discussionmentioning
confidence: 99%
“…Caffrey and Worthley (1927) Þrst reported that O. nubilalis adults are found in dense vegetation outside agricultural crops during the day. Although O. nubilalis adults may occupy irrigated cornÞelds in the western Corn Belt (Hunt et al 2001, Qureshi et al 2005, they usually colonize areas of dense grass in or bordering rain-fed cornÞelds in the Midwest (Showers et al 1976, DeRozari et al 1977 and Europe (Bontemps et al 2004, Dalecky et al 2006. These aggregation sites are where mating behaviors usually occur, including emission of female sex pheromone and copulation (Klun 1968, DeRozari et al 1977, Sappington and Showers 1983a.…”
mentioning
confidence: 99%
“…Some Lepidoptera adults may need to be squeezed to reveal the dye in the internal organs (through the intersegmental membranes of the abdomen) because the external scales do not pick up the dye. Oil-soluble dyes have been used to mark insects in the sterile insect release method (Steiner 1965, Schroeder et al 1974, in area-wide pest management programs Landin 1966, Hendricks et al 1971), and recently, in dispersal studies associated with resistance management programs in transgenic crops (Hunt et al 2001, Showers et al 2001, Qureshi 2003. Dyes have been used to mark insects in the following orders: Coleoptera (Gast and Landin 1966, Lloyd et al 1968, Daum et al 1969, Lepidoptera (Graham and Mangum 1971, Jones et al 1975, Ostlie et al 1984, Ramaswamy et al 1985, Showers et al 1989, Hunt et al 2000, Diptera (Steiner 1965, Schroeder et al 1974), Isoptera Mention of trade names or commercial products in this article is solely for the purpose of providing speciÞc information and does not imply recommendation or endorsement by Kansas State University or the U.S. Department of Agriculture.…”
mentioning
confidence: 99%
“…In this region, the corn borers spend a lot of time outside the corn Þelds. On the semiarid western high plains of North America, the European and southwestern corn borers seem to spend more time in the irrigated corn Þelds than in surrounding vegetation (Hunt et al 2001). Improved understanding of corn borer dispersal behavior is needed to ensure that this resistance management strategy will be effective in both regions.…”
mentioning
confidence: 99%
“…However, local (= nonmigratory) insect movement should be understood in order to effectively design and organize refuge plantings. For moths, one common method to study local population movement is the markrelease-recapture technique (Hunt et al 2001;Qureshi et al 2006).…”
mentioning
confidence: 99%